2011
DOI: 10.1111/j.1574-6941.2011.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of bacterial and fungal community structures in the rhizosphere of hybrid and standard rice cultivars and linkage to CO2 flux

Abstract: A field experiment was conducted with cultivation of hybrid and conventional cultivars in a rice paddy from China. Rhizosphere soil was sampled and CO 2 flux was measured at tillering (S1), grain filling (S2) and ripening (S3) across the growth stages. Microbial community structure, abundance and activity were analyzed using a combination of functional (enzymes) and denaturing gradient gel electrophoresis (DGGE) and real-time PCR molecular approaches. Invertase and urease activities, total microbial biomass ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 59 publications
4
22
0
1
Order By: Relevance
“…The decrease in these species directly led to the decrease in rhizosphere microbial diversity in Jiangxi. Ascomycota, Basidiomycota, and Zygomycota were the dominant fungal phyla, which was consistent with the findings of previous studies in citrus 34 Ascomycota and Basidiomycota are important fungi in most soils 35,36 , and the species in both phyla are involved in C cycling by degrading organic substances 37,38 . We observed significant differences in the relative abundance of Ascomycota and Basidiomycota in our samples; especially in Sichuan, the abundance of Ascomycota was the highest compared with that in the other three regions.…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in these species directly led to the decrease in rhizosphere microbial diversity in Jiangxi. Ascomycota, Basidiomycota, and Zygomycota were the dominant fungal phyla, which was consistent with the findings of previous studies in citrus 34 Ascomycota and Basidiomycota are important fungi in most soils 35,36 , and the species in both phyla are involved in C cycling by degrading organic substances 37,38 . We observed significant differences in the relative abundance of Ascomycota and Basidiomycota in our samples; especially in Sichuan, the abundance of Ascomycota was the highest compared with that in the other three regions.…”
Section: Discussionsupporting
confidence: 91%
“…Hussain et al . () also reported that Ascomycota dominated the fungal community in the rhizosphere of rice plants. In the present study, Ascomycota and Basidiomycota were found to be predominant across all of the fractions, which suggested a ubiquity of these species and an important role in agroecosystems.…”
Section: Discussionmentioning
confidence: 84%
“…The majority of the band types observed in the present study (B1‐B3, B11 and B13‐B17), particularly the dominant bands, were shared by all of the fractions, indicating that the bacterial community structure was highly stable. Sequencing of these bands revealed that Acidobacteria, Betaproteobacteria , Gammaproteobacteria and Chloroflexi were the predominant groups (Table ), and these genera are commonly found in rice paddies, as reported in previous studies by our group (Hussain et al ., ; Chen et al ., ). These findings indicate that these bacteria are widely distributed and survive well across all fractions and may play an important role in the turnover and stability of SOC.…”
Section: Discussionmentioning
confidence: 99%
“…The root system, the microorganisms and the soil form an underground micro-ecosystem in the rhizosphere [4]. The rhizosphere microbial community varies among plant species, growth stages and environmental habitats [5] and often includes plant growth-promoting bacteria (PGPB), which colonise plant roots [6]. Certain PGPR strains improve the ability of plants to adapt to a stressful environment [7], such as drought and salinity [8,9].…”
Section: Introductionmentioning
confidence: 99%